Is CD19-directed chimeric antigen receptor T cell therapy a smart strategy to combat central nervous system lymphoma? - Miyao, Kotaro; Yokota, Hirofumi; Sakemura, R. Leo (Frontiers in Oncology, 2023)
Primary central nervous system lymphoma (PCNSL) is a rare and aggressive type of diffuse large B-cell lymphoma (DLBCL) that occurs in both immunocompetent and immunocompromised adults. While adding rituximab to chemotherapeutic regimens resulted in a dramatic improvement in both progression-free survival and overall survival in patients with non-central nervous system (CNS) DLBCL, the outcomes of PCNSL are generally poor due to the immune-privileged tumor microenvironment or suboptimal delivery of systemic agents into tumor tissues. Therefore, the optimal therapy for PCNSL generally requires systemic therapy with sufficient CNS penetration, including high-dose intravenous methotrexate with rituximab or high-dose chemotherapy followed by autologous stem cell transplantation. However, overall survival is usually inferior in comparison to non-CNS lymphomas, and treatment options are limited for elderly patients or patients with relapsed/refractory disease. Chimeric antigen receptor T (CAR-T) cell therapy has emerged as a cutting-edge cancer therapy, which led to recent FDA approvals for patients with B-cell malignancies and multiple myeloma. Although CAR-T cell therapy in patients with PCNSL demonstrated promising results without significant toxicities in some small cohorts, most cases of PCNSL are excluded from the pivotal CAR-T cell trials due to the concerns of neurotoxicity after CAR-T cell infusion. In this review, we will highlight an overview of PCNSL, current approaches, resistance mechanisms, and future perspectives of CAR-T cell therapy in patients with PCNSL.